2021
DOI: 10.3389/fmicb.2021.728378
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Gap: Rare Lichens With Rare Cyanobionts – Unexpected Cyanobiont Diversity in Cyanobacterial Lichens of the Order Lichinales

Abstract: The last decades of research led to a change in understanding of lichens that are now seen as self-sustaining micro-ecosystems, harboring diverse microbial organisms in tight but yet not fully understood relationships. Among the diverse interdependencies, the relationship between the myco- and photobiont is the most crucial, determining the shape, and ecophysiological properties of the symbiotic consortium. Roughly 10% of lichens associate with cyanobacteria as their primary photobiont, termed cyanolichens. Up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Algal symbionts, by contrast, have been identified at species level for only a fraction of the symbioses for which fungal data are available. Only about 100 species have been named (Sanders & Masumoto, 2021), but DNA sequencing is uncovering evidence that phototroph diversity has been greatly underestimated (Muggia et al ., 2020; Jung et al ., 2021). Even so, patterns of phototroph occurrence are well enough resolved at a broad taxonomic scale that it is possible to construct a coarse matrix of the intersections of most symbiont match‐ups on these two branches of the tree of life.…”
Section: Diversity and Ecology Of Lichen Symbiosesmentioning
confidence: 99%
“…Algal symbionts, by contrast, have been identified at species level for only a fraction of the symbioses for which fungal data are available. Only about 100 species have been named (Sanders & Masumoto, 2021), but DNA sequencing is uncovering evidence that phototroph diversity has been greatly underestimated (Muggia et al ., 2020; Jung et al ., 2021). Even so, patterns of phototroph occurrence are well enough resolved at a broad taxonomic scale that it is possible to construct a coarse matrix of the intersections of most symbiont match‐ups on these two branches of the tree of life.…”
Section: Diversity and Ecology Of Lichen Symbiosesmentioning
confidence: 99%
“…Al Amin et al, 2021). However, the two strains investigated here are the first strains of this genus described from a desert environment, while the other species of the genus have multiple origins, including lichen symbioses (Jung et al, 2021a;Soares et al, 2021;Panou and Gkelis 2022). All of them have a very complex life cycle in common that can hamper biotechnological applications due to different metabolic activity depending on the developmental stage of the culture.…”
Section: Phylogenetic and Taxonomical Remarksmentioning
confidence: 99%
“…is the only genus in this family and is symbiosed with the cyanobacterial photobiont known as Chroococcidiopsis, Myxosarcina, Gloeocapsa [2][3][4][5] or Chroococcales [6][7][8]. Through isolation and culture of lichen specimens and the construction of phylogenetic trees, Jung et al [9] identified cyanobionts of Peltula as Aliterella and Compactococcus gen. nov., Pseudocyanosarcina gen. nov., and an unknown species, but did not find Chroococcidiopsis, which is the only known unicellular terrestrial genus and could be considered robust support to delimit the genus Peltula.…”
Section: Introductionmentioning
confidence: 99%